2012
DOI: 10.1590/s1806-66902012000400009
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between apparent soil electrical conductivity and soil properties

Abstract: -Precision agriculture that is based on the physical and chemical properties of soil requires a dense sampling to evaluate spatial variability in the field. This dense sampling is often expensive and time consuming. One technique to reduce the number of samples is to define management zones based on information that is collected in the field. Some researchers have demonstrated the importance of the electrical properties of soil in defining management zones. Thus, the objective of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
11
0
4
Order By: Relevance
“…Many studies have reported the relationship of EC a with other soil attributes, including texture, water content, salinity, pH, cation exchange capacity (TERRÓN et al, 2011;HEIL;SCHMIDHALTER, 2011;ISLAM et al, 2012;SERRANO et al, 2012;VALENTE et al, 2012a) and crop yield (MANN et al, 2011;ALCÂNTARA et al, 2012). Therefore, EC a mapping may provide a rapid and effective means of identifying areas with similar features at a lower cost, allowing for needsbased management (FAROOQUE et al, 2012;VALENTE et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the relationship of EC a with other soil attributes, including texture, water content, salinity, pH, cation exchange capacity (TERRÓN et al, 2011;HEIL;SCHMIDHALTER, 2011;ISLAM et al, 2012;SERRANO et al, 2012;VALENTE et al, 2012a) and crop yield (MANN et al, 2011;ALCÂNTARA et al, 2012). Therefore, EC a mapping may provide a rapid and effective means of identifying areas with similar features at a lower cost, allowing for needsbased management (FAROOQUE et al, 2012;VALENTE et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Soil particles were determined using the methods described by soil survey staff [16], w here three fractions (sand, silt, clay) were separated. Soil pH H2O as well as electrical conductivity (EC) were measured in an aqueous solution at a soil/distilled water ratio as 1:2.5, [17]. Moreover, pH was additionally [20][21].…”
Section: Soil Chemical Analysesmentioning
confidence: 99%
“…Portanto, ela se relaciona à textura, à capacidade de troca catiônica, ao conteúdo de água, à salinidade, e à declividade e acidez do solo (Lund et al, 1999;Valente et al, 2012;. No entanto, essas relações são, geralmente, intrínsecas a cada tipo de solo e local investigado (Moral et al, 2010).…”
Section: Introductionunclassified
“…Ainda, como a CE apresenta elevada relação com a CEa (Lund et al, 1999), o sensoriamento em tempo real poderia reduzir o tempo e os gastos com a amostragem intensa de solo e suportaria a adoção de estratégias de manejo sítio-específico na cultura do milho (Zea mays L.), tais como a escolha de híbridos, a definição da população de plantas e os níveis de fertilização nitrogenada (Peralta et al, 2015). Contudo, trabalhos com sensoriamento em tempo real do solo, por CEa, ainda são pontuais e em Latossolos do Centro-Oeste (Brandão et al, 2011;Valente et al, 2012;Sana et al, 2014) e, portanto, insuficientes para recomendações em regiões distintas daquelas investigadas, como é o caso dos Latossolos do Sul do Brasil.…”
Section: Introductionunclassified